RECYCLING OYSTER SHELLS AND RED SCORIA STONE FOR BIO-DENITRIFICATION PROCESS IN WASTEWATER TREATMENT - Thi Kim Quyen Vo; Ngoc Huy Nguyen; Ngoc Hoa Pham; Tan Phong Nguyen (HUIT Journal of Science, 2025)
Various media have recently been used to treat nitrogen from wastewater. However, low removal efficiency and operation problems remain challenging when applied at wastewater treatment plants. Natural materials for nitrogen removal have become potential under current sustainable development. Consequently, this study utilized red scoria stone and sulfur-based carriers made from oyster shells for nitrate treatment. Red scoria stones are referred to treat wastewater containing a high C/N (organic carbon/nitrogen) ratio, meanwhile, sulfur-based carriers made from oyster shells are suitable for wastewater containing a low C/N ratio, even with no organic carbon. The nitrate removal rate reached 270 ± 20 g N/m3.day for packed-bed bioreactor filled with red scoria stone (PBR–stone) and 260 ± 10 g N/m3.day for packed-bed bioreactor filled with sulfur-based carriers (PBR–carrier). These nitrate removal rates are higher than those of the other media used to treat nitrate from wastewater. Additionally, 88 ± 3% of organic compounds removed in PBR–stone and no external organic carbon added to PBR–carrier are strengths of these media. Recycling these solid wastes creates a new material for wastewater treatment and promotes sustainable development.